Feasibility of oxygen saturation related diffusion index for monitoring oxygenation status in patients with acute respiratory distress syndrome (应用指氧饱和度相关弥散指数监测急性呼吸窘迫综合征患者氧合状态的可行性研究) - WANG Hongxia (王红霞); GAO Chenxue (高晨雪); LI Wanjun (李婉君); LI Ying (李莹); WANG Ying (王颖); LU Meijia (卢美佳); YAN Xiaoyang (颜晓阳); LI Guo (励国) (Journal of International Translational Medicine Limited, 2021)
Objective To analyze the clinical value of oxygen saturation related diffusion index for monitoring oxygen and status in patients with acute respiratory distress syndrome(ARDS). Methods The enrolled cases were 130 patients with ARDS treated in the hospital from May 2017 to January 2020. The oxygen saturation related diffusion indexes were assessed and compared between patients with mild, moderate and severe ARDS. Results Of the 130 patients with ARDS, 38 were mild, accounting for 29. 23%; 55 were moderate, accounting for 42. 31%; and 37 were severe, accounting for 28. 46%. Refers to oxygen saturation-related diffusion index, mild ARDS patients were significantly higher than moderate patients, moderate patients were significantly higher than severe patients(P＜0. 05). Conclusion Finger oxygen saturation-related diffusion index has a negative correlation with the condition of patients with ARDS. Strengthening the monitoring of finger oxygen saturation-related diffusion index is of great significance for assessing the condition, treatment effect and prognosis of ARDS patients. (目的 分析应用指氧饱和度相关弥散指数监测急性呼吸窘迫综合征(ARDS)患者氧合状态的临床价值。方法 选取医院2017年5月-2020年1月收治的130例ARDS患者为研究对象, 对比轻度、中度、重度ARDS患者指氧饱和度相关弥散指数。结果 130例ARDS患者中38(29. 23%)例轻度, 55(42. 31%)例中度, 37(28. 46%)例重度。指氧饱和度相关弥散指数: 轻度ARDS患者明显高于中度患者, 中度患者明显高于重度患者, 差异有统计学意义(P<0. 05)。结论 指氧饱和度相关弥散指数与ARDS患者的病情呈负相关性, 加强指氧饱和度相关弥散指数监测, 对于评估ARDS患者病情、治疗效果、预后等具有重要意义。)